Techniques for improving pronunciation of the past tense ending of the regular verbs in students of the eighth grade at IPTC 2014 - Moreno Pitty, Yorlenis Yaneth; González Batista, Johanna Aneth; De Gracia, Prof. Edward (David, Panamá : UDELAS, 2014)
The main purpose of this investigation is to identify strategies that can help language students acquiring the correct pronunciation of the simple past tense endings of regular verbs in Basic English second level. After recognizing the most common pronunciation difficulties, several strategies were selected to work with learners in order to help them improve pronunciation so that communication with others, native or nonnative, become successful.
TABLE CONTENT GRAPHIC INDEX GRAPHIC TABLE INTRODUCTION CHAPTER I: ANTECEDENT AND STATEMENT OF THE PROBLEM 1.1. Antecedent 1.2. Description of the problem 1.3. Problem formulation 1.4. Justificaciton 1.4.1. Importance 1.4.2. Contributions 1.5. Delimitation and scope 1.6. Objectives 1.6.1. General objectives 1.6.2. Specific objectives 1.7. Methodology aspects 1.7.2. Kind if investigation 1.7.3. Population 1.7.4. Instrument 1.7.5. Observation guide 1.7.6.. Check list CHAPTER II: THEORICAL FRAMEWORK 2.1. Technique 2.1.1. Drill 2.1.2. Color-coding system 2.1.3. Sound sort 2.2.4. Phonetic circle 2.2.5. Dictation competence 2.2. Resource to develop techniques 2.3. Activities for developing techniques 2.4. Time for the development of techniques 2.5. Self-confidence 2.2. Rules of the regular verbs in past tense 2.2.1. List of regular verbs 2.2.2. Classification of the verbs accorading to their endings 2.2.3. Pronunciation of regular past tense verbs 2.2.4. Analisis of the importance of having a right pronunciation 2.3. Attitude from teachers and students toward pronunciation 2.3.1. Motivation 2.3.2. Exposure to target language 2.3.3. Integration of english pronunciation into the curriculum 2.4. Inflectional morphology means 2.4.1. Morpheme 2.4.2. Approaches toward the morphemes and morphology work on 2.4.2.1. Morpheme-based morphology 2.4.2.2. Lexeme-based morphology 2.4.2.3. Word-based morphology 2.4.3. Type of morpheme 2.5. Teacher's role as facilitatot of motivation 2.5.1. Impact of motivation on pronunciation english language 2.5.2. Impact of the motivation on learners 2.5.3. Relationship between learning styles and motivation CHAPTER III: METHODOLOGICAL ASPECTS 3.1. Type of research 3.2. Information sources 3.2.1. Material sources 3.2.2. Human sources 3.3. Technique for improving the past tense ending pronunciation of regular verbs in students of the eight grade at IPTC, 2014 3.3.1. Conceptual definition 3.3.2. Instrumental definition 3.3.3. Operational definition 3.4. Features of the past tense ending pronunciation regular verbs in students of eight grade at IPTC 2014 3.4.1. Conceptual definition 3.4.2. Instrumental definition 3.4.3. Operational definition 3.5. Factors that influence in the pronunciation of the past tense ending regular verbs in students of eight grade at IPTC 3.5.1. Conceptual definition 3.5.2. Instrumental definition 3.5.3. Operational definition 3.6. L2 acquisition of inflectional morphology of the past tense endings regular verbs 3.6.1. Conceptual definition 3.6.2. Instrumental definition 3.6.3. Operational definition 3.7. Expalin the motivation effect of the techniques for teaching pronunciation 3.7.1. Conceptual definition 3.7.2. Instrumental defilnition 3.7.3. Operational definition CHAPTER IV: ANALYSIS AND RESULTDS 4.1. Interpretation of the interview to english teacher 4.1.1. Technique for improving the past tense ending pronunciation of regular verbs in students of the eight grade al IPTC 2014 4.1.2. Features of the past tense ending pronunciation regular verbs in students of eight grade at IPTC, 2014 4.1.3. Factors that influence in the pronunciation of the past tense ending regular verbs in students of eight grade al IPTC 4.1.4. L2 acquisition of inflectional morphology of the past tense endings regular verbs 4.1.5. To expalin motivation effect to the techniques for teaching pronunciation 4.2. Analysis of the checklist applied to the students of eight level at, IPTC 4.2.1. Pronunciation of the ending sound/id/ 4.2.2. Pronunciation of the ending sound/d/ 4.2.3. Pronunciation of the endign sound/t/ CONSLUSIONS RECOMENDATIONS BIBLIOGRAPHY
Incluye Table contents
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés.
Incluye Bibliografía
No se presta a domicilio.
No se saca fotocopias.
Keywords: ENGLISH -- TESIS; INGLÉS -- TESIS; PHONOLOGY -- TESIS; INGLES -- TESIS -- PRONUNCIACIÓN; LICENCIATURA EN DOCENCIA EN INGLÉS - TESIS; IPTC; REGULAR VERBS - PAST TENSE